Heart Failure With Preserved Ejection Fraction in Hypertension Patients: A Myocardial MR Strain Study. Issue 2 (7th September 2020) - He, Jian; Sirajuddin, Arlene; Li, Shuang; Zhuang, Baiyan; Xu, Jing; Zhou, Di; Wu, Weichun; Sun, Xiaoxin; Fan, Xiaohan; Ji, Keshan; Chen, Lin; Zhao, Shihua; et al.
Abstract : Background: Despite current recommendations for heart failure with preserved ejection fraction (HFpEF), few studies have demonstrated the ability of MRI to identify subtle functional differences between HFpEF with essential hypertension (HFpEF‐HTN) patients and hypertension patients (HTN). Purpose: This study aimed to detect and evaluate HFpEF in patients with HTN using feature‐tracking (FT) and to ascertain optimal strain cutoffs for the diagnosis of HFpEF‐HTN. Study Type: Retrospective study. Population: Three groups (84 with HFpEF‐HTN; 72 with HTN; and 70 healthy controls). Field Strength: 1.5T, steady‐state free precession (SSFP), and half‐Fourier single‐shot turbo spin‐echo (HASTE) sequences. Assessment: All patients underwent laboratory testing and imaging protocols (echocardiography and MRI). FT‐derived left ventricular (LV) strain and strain rate (SR) were measured and compared among the three groups with adjustment for confounding factors. Statistical Tests: Kolmogorov–Smirnov's test, independent‐sample t ‐tests, one‐way analysis of variance (ANOVA), Pearson's correlation coefficient, area under the receiver‐operator characteristic (ROC) curve (AUC), and logistic regression. Results: Compared to 72 HTN patients and 70 healthy controls, HFpEF‐HTN patients (84 patients) demonstrated significantly impaired LV strains (except for global peak systolic radial strain, GRS, P < 0.05 for all). Only LV global peak systolic longitudinal strain (GLS) was significantly impaired in HTN patients vs. controls ( P < 0.05). The global peak systolic circumferential SR (sGCSR) showed the highest diagnostic value for the differentiation of HFpEF‐HTN patients from HTN patients (AUC, 0.731; cutoff value, −1.11/s; sensitivity, 56.0%; specificity, 84.7%). Only global peak early diastolic longitudinal SR (eGLSR) remained independently associated with a diagnosis of HFpEF‐HTN in multilogistic analysis. The major strain parameters significantly correlated with LV ejection fraction, end‐systolic volume index, and N‐terminal pro‐brain natriuretic peptide ( P < 0.05 for all) and also demonstrated differences between NYHA functional class. Data Conclusion: HFpEF‐HTN patients suffer from both systolic and diastolic cardiac dysfunction. FT‐derived strain parameters have potential value for the diagnosis and risk stratification of HFpEF‐HTN patients. Level of Evidence 3. Technical Efficacy Stage 2.